Blood Profile of Broilers Given Feed Containing Fish Meal With Different Levels - Wardani, Ismi; Saili, Takdir; Pagala, Muhammad Amrullah (Pascasarjana Universitas Sulawesi Tenggara, 2021)
The study aims to analyze the blood profile of broilers fed with fishmeal with different levels. The study used a complete randomized design (RAL) 4 treatments and 4 replays with 2 chickens as an experiment and broiler chickens as many as 100 heads, the treatment in the study was P0= Control (commercial feed BP11), P1 = 43 % Yellow Corn + 21% Bran + 27% CAB + 9% FishMeal, P2 = 43% Yellow Corn + 23% Bran + 22% CAB + 12% Fishmeal, P3 = 43% Yellow Corn + 25% Bran + 17% CAB + 15% Fishmeal with observed parameters is leukocyte differential. The results of the study with feeding containing fishmeal levels differed markedly (P<0.05) on the value of eosinophils, but had no real effect (P>0.05) on the value of hematocrit, lymphocytes, heterophiles, monocytes, basophils and H / L values.